WHEN BURNOUT DRIVES DELAY: UNPACKING ACADEMIC PROCRASTINATION IN JUNIOR HIGH SCHOOL STUDENTS - Cristy Winata; Rani Mega Putri (Universitas Negeri Surabaya, 2025)
Academic burnout is a condition frequently encountered by students during the learning process at school, which can lead to academic procrastination. This study aims to examine the relationship between academic burnout and academic procrastination among grade VIII students at Indralaya 1 Public Junior High School. Quantitative method with correlational design was used, involving 171 students from 9 classes. The research instruments were burnout and academic procrastination scales distributed through Google Form. As a result, most students experienced burnout (37%) and academic procrastination (38%) in the moderate category. The correlation between the two variables was -0.521, indicating a negative or opposite relationship. This suggests that as academic burnout increases, academic procrastination tends to decrease, and vice versa. This research is anticipated to serve as a guideline for schools and teachers in addressing the issues of burnout and academic procrastination